2012
DOI: 10.1124/jpet.112.196717
|View full text |Cite
|
Sign up to set email alerts
|

Central Mechanisms of Menthol-Induced Analgesia

Abstract: Menthol is one of the most commonly used chemicals in our daily life, not only because of its fresh flavor and cooling feeling but also because of its medical benefit. Previous studies have suggested that menthol produces analgesic action in acute and neuropathic pain through peripheral mechanisms. However, the central actions and mechanisms of menthol remain unclear. Here, we report that menthol has direct effects on the spinal cord. Menthol decreased both ipsilateral and contralateral pain hypersensitivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 38 publications
(60 reference statements)
6
79
1
Order By: Relevance
“…Both ligand-gated and voltagegated channels are inhibited by menthol (IC 50 5 297 mM for Na 1 channels and IC 50 5 125 mM for Ca 21 channels in dorsal horn neurons) (Pan et al, 2012). Moreover, the effective concentrations observed in the current study were found to be comparable with menthol concentrations sufficient to activate TRPM8 channels, with EC 50 values ranging between 67 and 196 mM (Sherkheli et al, 2010) in X. laevis oocytes.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Both ligand-gated and voltagegated channels are inhibited by menthol (IC 50 5 297 mM for Na 1 channels and IC 50 5 125 mM for Ca 21 channels in dorsal horn neurons) (Pan et al, 2012). Moreover, the effective concentrations observed in the current study were found to be comparable with menthol concentrations sufficient to activate TRPM8 channels, with EC 50 values ranging between 67 and 196 mM (Sherkheli et al, 2010) in X. laevis oocytes.…”
supporting
confidence: 54%
“…Recent electrophysiological studies reported that menthol inhibits the functions of Na 1 (Gaudioso et al, 2012;Pan et al, 2012) and Ca 21 channels (Pan et al, 2012) in a voltage-dependent manner. The effect of changing the membrane potential relationship between 5-HT-activated current and membrane potential before and after 10-minute menthol (300 mM) application is Menthol on 5-HT 3 Receptor shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although precise concentrations of menthol in the brains of smokers are unknown, the results of an animal study show that menthol can readily penetrate the central nervous system. For example, Pan et al (2012) showed that menthol can reach high levels in the brains of mice within 5 minutes of a bolus intraperitoneal injection and was still measurable 60 minutes after injection.…”
Section: Discussionmentioning
confidence: 99%